Integration of Reproductive Biology and Mental Health Concepts in Learning: A Study of Baby Blues Postpartum Caesarean Delivery - Hafid, Wahyuni; Safitri, Dewi; Fony, Fony; Susiati, Asih Luklu (Universitas Negeri Makassar, 2025)
The phenomenon of postpartum baby blues is a mild mood disorder that is commonly experienced by mothers after childbirth, especially in mothers who undergo cesarean delivery. This condition occurs due to drastic hormonal changes, physical pain, a longer recovery process, as well as psychosocial factors such as low emotional support and feelings of loss of control during the labor process. This issue has not been widely integrated in the learning of reproductive biology in higher education, which tends to focus on physiological aspects. This study aims to review the scientific literature on the prevalence of post-caesarean baby blues and explore its potential as a learning issue in reproductive biology. The method used is Systematic Literature Review (SLR) using content analysis of 16 relevant and published scientific articles in the period 2015–2025. The results of the study showed that post-caesarean mothers had a higher risk of experiencing baby blues compared to normal childbirth. In addition, the integration of this issue in reproductive biology learning has strategic value in fostering empathy, science literacy, and mental health awareness of students. This study recommends the application of project-based learning models and case studies as an effective approach to raise the issue of baby blues in the curriculum in higher education. Keywords: reproductive biology, baby blues, mental health, caesarean, higher education